Evaluation of preventive effect of dexpanthenol in radiation injury by lung perfusion scintigraphy - Koc, Z.; In, E.; Ucer, O.; Karslioglu, I.; Canpolat, S. (Springer, 2015)
[Abstract Not Available]
28th Annual Congress of the European-Association-of-Nuclear-Medicine (EANM) -- OCT 10-14, 2015 -- Hamburg, GERMANY